Use of Medicinal Plants by Cancer Patients Under Chemotherapy in the Northwest of Morocco (Rabat Area) : Cross-Sectional Study - Nadia El Orfi (Phd Student); Saber Boutayeb MD, PhD; Bouchra Haddou Rahou PhD; Hassan Errihani MD, PhD (SAGE Publishing, 2022)
Background Variety of conventional treatments are used to treat cancer. Cancer patients adopt other alternative therapies including medicinal plants. Their curative power results in the presence of secondary metabolites in its different parts. However, they can have toxic effects and interactions with conventional treatment and even chemosensitivity of the cancer cells. Objectives This study aims to determine the prevalence of the use of medecinal plants by cancer patients undergoing chemotherapy, list the medecinal plants used, identify the most consumed, present the reported adverse effects and determine the predictive factors of their use. Materials and Methods This was a cross-sectional study of 203 patients followed at the National Institute of Oncology in Rabat from 01 October 2018 to 30 November 2018. Regarding socio-demographic and clinical characteristics and data on the use of medicinal plants were collected from a questionnaire. Findings of 203 patients, 37% used medicinal plants. 30 plants also the honey were identified during this study. The "euphorbia honey"was consumed at (40%), The most used plants were garlic (13%), turmeric, fenugreek and thyme (11% each). 5% of patients presented side effects related to the consumption of medicinal plants. There is a significant association between the use of medicinal plants and socio-economic level (p  =  0.004) and duration of illness (p  =  0.048). Conclusion This study revealed a high prevalence of medicinal plants used by cancer patients receiving chemotherapy at National Institute of Oncology. The more clinical studies are desirable to demonstrate the efficacy of medicinal plants and their therapeutic effects to encourage their consumption or prohibit them.